Spontaneous rotational inversion in Phycomyces. - Goriely, A; Tabor, M (2011)
The filamentary fungus Phycomyces blakesleeanus undergoes a series of remarkable transitions during aerial growth. During what is known as the stage IV growth phase, the fungus extends while rotating in a counterclockwise manner when viewed from above (stage IVa) and then, while continuing to grow, spontaneously reverses to a clockwise rotation (stage IVb). This phase lasts for 24-48 h and is sometimes followed by yet another reversal (stage IVc) before the overall growth ends. Here, we propose a continuum mechanical model of this entire process using nonlinear, anisotropic, elasticity and show how helical anisotropy associated with the cell wall structure can induce spontaneous rotation and, under appropriate circumstances, the observed reversal of rotational handedness.